Effectiveness of Web- and Mobile-Based Treatment of Subthreshold Depression With Adherence-Focused Guidance: A Single-Blind Randomized Controlled Trial. Issue 1 (January 2018) - Ebert, David Daniel; Buntrock, Claudia; Lehr, Dirk; Smit, Filip; Riper, Heleen; Baumeister, Harald; Cuijpers, Pim; Berking, Matthias
Abstract: Evidence for the impact of psychological Interventions for subthreshold depression (sD) is conflicting. Moreover, human resources to deliver such treatments are limited. This study aimed to evaluate the effectiveness of a web-based intervention with adherence-focused guidance in the treatment of sD. Participants with sD (CES-D ≥ 16, no Major Depressive Disorder according to DSM-IV criteria, N = 204) recruited via a large health insurance were randomly allocated to a web-based mobile-supported cognitive-behavioral intervention or to a waitlist control condition with unrestricted access to usual care. The primary outcome was the reduction in depressive symptom severity as measured by blind diagnostic raters using the Quick Inventory of Depressive Symptomatology (QIDS) at posttreatment. There was a statistically significant between-group difference in QIDS scores at posttreatment in favor of the intervention group, F(1, 201) = 11.31, p = .001, corresponding to a medium effect size of d = 0.37 (95% CI 0.09–0.64) and a NNT of 7 (95%–CI 3.7–41.2). Significant effects in favour of the intervention group were also found for secondary outcomes such as quality of life, anxiety, and insomnia severity. Web-based self-help interventions with adherence-focused guidance could be an acceptable and effective approach to reduce a range of negative consequences associated with subclinical depression. Highlights: A web-based CBT intervention is effective in treating subthreshold depression. Self-report and observer-based ratings yield significant effects on symptom severity. Adherence-focused guidance is acceptable to participants.